The personal vote, electoral experience, and local connections: Explaining retirement underperformance at UK elections 1987–2010. (May 2019) - Middleton, Alia
At each election, some Members of Parliament (MPs) decide to step down. Irrespective of their motivation, retirement has an electoral impact; their party's constituency vote share experiences a 'slump'. Conventional wisdom attributes this underperformance to the loss of the retiring MP's personal vote. This article uses aggregate-level data covering UK general elections between 1987 and 2010 to demonstrate whether this explanation is supported. It also examines whether political parties can mediate such underperformances by considering the electoral experience and local connections of candidates contesting the post-retirement election. The article finds mixed evidence for the link between personal votes and underperformance. However, parties should pay close attention to the candidates selected to fight the post-retirement election. If an inheritor wants to win a national government or opposition seat, experience and local ties can be harmful. Also, schooling and other local ties enable candidates to mount effective challenges to government and opposition inheritors.